Improved Ohmic contact to GaN and AlGaN/GaN two‐dimensional electron gas using trap assisted tunneling by B implantation. Issue 5 (20th March 2015) - Upadhyay, Pankaj; Meer, Mudassar; Takhar, Kuldeep; Khachariya, Dolar; Kumar S, Akhil; Banerjee, Debashree; Ganguly, Swaroop; Laha, Apurba; Saha, Dipankar
<x xml:space="preserve">Abstract</x> We have demonstrated that deep level traps created by B implantation can reduce the contact resistance by forming an additional path for electron transport via trap assisted tunneling in GaN and AlGaN/GaN heterostructures. B implantation by plasma‐immersion ion implantation creates deep level traps 0.36 eV below the conduction band edge to a shallow depth (10–25 nm) in the structure. These traps act as efficient percolation path for electrons between the TiN Ohmic contact and the active region, which can be bulk GaN or a two‐dimensional electron gas (2DEG) formed at the AlGaN/GaN heterostructure. The improved Ohmic behavior is manifested as reduced specific contact resistivity and normalized contact resistance. The specific contact resistance and the normalized contact resistance are found to decrease by 59% (30%) and 86% (51%), respectively, for bulk GaN (AlGaN/GaN). The effect of B implantation on the sheet resistance of the 2DEG is insignificant when the implantation energy and post‐implantation annealing time are controlled optimally.